Hedonic value motivation: impact on consumers’ purchase intention - Wiwik Handayani; Musnaini Musnaini; Wahyudan Iswara Praditya (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
The focus of this study, using an explanatory and accidental approach, shows consumer buying interest in shopping at modern shopping centers in Surabaya. Data were collected from 90 questionnaires and analysed using the Partial Least Square (PLS). The results of the study showed that consumer buying interest at the modern shopping centers (malls) was driven by hedonic impulses. It is evident from the positive significance value associated with consumer perceptions of the atmosphere of the outlet, of retail services, as well as the presence of fashion that contains hedonist value so as to have an effect on consumers’ purchase intentions. For future studies, it is best to examine utilitarian aspects as a motivation that affects the purchasing intention of consumers at modern shopping centers